Simultaneous Bilateral Transient Osteoporosis of the Hip without Pregnancy - Yasuaki Okada; Sachiyuki Tsukada; Masayoshi Saito; Atsushi Tasaki (Case Reports in Orthopedics)
Transient osteoporosis of the hip (TOH) is a rare disorder characterized by acute severe coxalgia and temporary osteopenia in the proximal femur. Although most cases were unilateral or staged bilateral TOH, some authors reported that the pregnant patients simultaneously had TOH in their bilateral hips. However, there has been no report of simultaneous bilateral TOH in the patient without pregnancy. A 25-year-old Japanese woman without pregnancy had acute simultaneous bilateral hip pain. Plain X-ray of the bilateral hips did not show a periarticular osteopenia. However, magnetic resonance image obtained one week after the onset demonstrated increased T2-weighted signal intensity and decreased T1-weighted signal intensity in the bilateral femoral heads. She was treated conservatively, and follow-up magnetic resonance image at seven weeks after the onset returned to normal bone marrow signal intensity. Her bilateral coxalgia subsided gradually. At one year after the onset, she had no sign of symptomatic flair. Our experience with this case indicates that recognizing the possibility of simultaneous bilateral TOH is important unless the patient is pregnant, and magnetic resonance image is predictable test to make a diagnosis of TOH, even in the absence of abnormal finding on plain X-ray.